Wealth Inequality and Altruistic Bequests - Laitner, John (American Economic Review, 2002)
This paper examines the role of bequests and inter vivos gifts in the U.S. economy, considering their importance in determining (i) the economy’s aggregate capital stock, (ii) the distribution of private net worth, and (iii) public policy outcomes and options. It focuses on several recent calibrated simulations.(This abstract was borrowed from another version of this item.)